2004
DOI: 10.2174/0929867043365080
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1: A Novel Therapeutic Target in Oxidative Tissue Injuries

Abstract: Oxidative stresses such as oxidant stimuli, inflammation, exposure to xenobiotics, or ionizing irradiation provoke cellular protective responses, principally involving transcriptional activation of genes encoding proteins which participate in the defense against oxidative tissue injuries. Excess of free heme, which is released from hemeproteins under such conditions, may constitute a major threat because it can catalyze the formation of reactive oxygen species (ROS). Exposure of mammalian cells to oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(120 citation statements)
references
References 0 publications
6
111
0
3
Order By: Relevance
“…HO-1 is regarded as a regulatory protein during inflammatory situations (25,26). Therefore, the initial induction of HO-1 after TNF-· stimulation demonstrated in the present study is suggested to be a counter-regulation to avoid overstimulation of the proinflammatoric state of the cells.…”
Section: Discussionmentioning
confidence: 53%
“…HO-1 is regarded as a regulatory protein during inflammatory situations (25,26). Therefore, the initial induction of HO-1 after TNF-· stimulation demonstrated in the present study is suggested to be a counter-regulation to avoid overstimulation of the proinflammatoric state of the cells.…”
Section: Discussionmentioning
confidence: 53%
“…HO-1 is highly inducible by heme and a vast array of non-heme substances, including LPS. By contrast, HO-2 is expressed in a constitutive fashion, and appears to function as a heme-binding molecule in normal cells (19). The similarities and diversities of the NO/NOS and CO/ HO systems were well established in numerous studies (11,14), but the interactions between these systems have not yet been elucidated.…”
Section: Real-time Reverse Transcriptase-polymerase Chain Reaction (Rmentioning
confidence: 99%
“…Of these genes, heme oxygenase 1 (HMOX1) and activating transcription factor 3 (ATF3) showed remarkable overexpression (more than 8-fold) by high-concentration treatment at all 3 time points. HMOX1 was previously reported to be induced in kidney following toxic and ischemic insults (Nath, 2006, Takahashi et al, 2004.…”
Section: Discussionmentioning
confidence: 98%